(untitled) (Prilozi za orijentalnu filologiju, 2025)
The paper presents a hitherto unpublished treatise entitled Kašf al–ʼasrār bi ḥaqāʼiq al–kitāb wa daqāʼiq al–ṭahāra (Discovering the secrets of meanings of the word book and characteristics of the word purity), written in the second half of the 18th century by Muhamed Son of Mustafa Čajničanin (Muḥammad Ibn Muṣṭafā al–Čāyničawī). There are several references in literature about the author, suggesting that he served as a mudarris and a Sarajevo mufti. He also authored a fairly known work on logic. His treatise discussed in this paper has so far not been a subject of textological preparation and content analysis, although it has been registered. For the purposes of this paper, two copies of the work were used as sources, of which one is held in the manuscript collection of the Gazi Husrev–Bey’s Library in Sarajevo, and the other in the collection of manuscripts in oriental languages of the University Library “Svetozar Marković” in Belgrade. The study includes the description and textological preparation of the two available copies of the manuscript, critical examination of the work, translation and content analysis, focusing on the analysis of the kitāb al–ṭahāra construct state, as well as the form and meanings of its components.